“A hysterical spinster of mature age”: 1 Some reflections on recent biographies of Emily Hobhouse (Historia, 2021)
While the first (auto)biography of the heroine of the Afrikaner people, Emily Hobhouse was published a mere three years after her death in 1929, and a steady stream has followed since, in the last three years or so there has been a remarkable resurgence in popular accounts of her life and work. This review essay profiles three of the latest biographies written by Robert Eales, Elsabe Brits and Jennifer Hobhouse Balme, and variously examines her role in the South African War and her ideas on pacifism, war and politics.
Keywords: Emily Hobhouse; South African War; humanitarianism; First World War; Tibbie Steyn; Jan Smuts